Вимірювання соціального статусу особи за допомогою суб’єктивного методу визначення соціального статусу - Ковальська, Єлєна; Новосьолова, Ольга; Суванова, Анна; Старостіна, Юлія; Kovalskaya, Yeliena; Novosolova, Olga; Suvanova, Anna; Starostina, Yulia; Kovalska, Yeliena; Novosolova, Olha; Suvanova, Anna; Starostina, Yuliia (My University, 2016)
Дослідження власного сприйняття респондентами своєї позиції в соціальній ієрархії дає змогу оцінити ступінь нерівності в суспільстві, отримати загальне уявлення про соціальну структуру конкретного суспільства. Суб’єктивний метод оцінки соціального статусу особи дає змогу оцінити соціально-економічні характеристики в міру їх впливу на формування положення особи в соціальній структурі. Емпіричним підтвердженням зазначених тез є результати дослідження соціального статусу особи в суб’єктивному вимірі, яке проводилося серед студентів Київського національного університету імені Тараса Шевченка у формі онлайн-опитування у 2016 р. Серед висновків потрібно виокремити такі: більшість респондентів (51 %) відносить себе до середнього класу; найбільш значущими складовими частинами соціального статусу названо матеріальні статки (72 %), рівень освіти (66 %), рід діяльності (53 %); також наведено суб’єктивну ієрархію рівня престижності родів діяльності. Висновки щодо суб’єктивної оцінки соціального статусу можуть бути надалі використані в дослідженнях соціальної структури українського суспільства, зокрема в порівнянні результатів вимірювання за допомогою суб’єктивних та об’єктивних методів оцінки. The study of social status of the person in Ukraine is becoming increasingly relevant. This is due to the need to explain the behavior and values of the individual through its objective characteristics as single-items criteria (age, sex, education) and Multicriteria (social status). Objective method social status measurement in the theoretical and empirical aspects was described earlier in articles (Sydorov, Sokolovskaya, 2013). This article is devoted to the research results of social status measurement in Ukraine by subjective methods. Investigation own perception of one’s position in the social hierarchy makes it possible to assess the degree of inequality in society, gives overview of the social structure of a particular society. Subjective method of measurement a person's social status gives the opportunity to assess the characteristics according to the degree of their influence on the one’s position in the social structure. The survey was conducted among students of the Kyiv National Taras Shevchenko University in the form of an online survey in 2016. Among the findings are the following in particular: the majority of respondents (51 %) consider themselves as middle class; the most important components of social status were: material wealth (72 %), education (66 %), and occupation (53 %); also provides a subjective hierarchy of prestige occupation. Findings of subjective evaluation of social status can be further used in studies of the social structure of Ukrainian society, particular in comparing measurement results of subjective and objective measurement methods.
Person’s Social Status Measurement of by Methods of Subjective Social Status Measurement
Keywords: вимірювання соціального статусу; суб’єктивний соціальний статус; соціальний статус в Україні; measurement of social status; subjective social status; social status in Ukraine